Neuromodulatory Effects of Transcranial Direct Current Stimulation on Motor Excitability in Rats. (17th December 2019) - Liu, Hui-Hua; He, Xiao-Kuo; Chen, Hsin-Yung; Peng, Chih-Wei; Rotenberg, Alexander; Juan, Chi-Hung; Pei, Yu-Cheng; Liu, Hao-Li; Chiang, Yung-Hsiao; Wang, Jia-Yi; Feng, Xiao-Jun; Huang, Ying-Zu; et al.
Abstract : Transcranial direct current stimulation (tDCS) is a noninvasive technique for modulating neural plasticity and is considered to have therapeutic potential in neurological disorders. For the purpose of translational neuroscience research, a suitable animal model can be ideal for providing a stable condition for identifying mechanisms that can help to explore therapeutic strategies. Here, we developed a tDCS protocol for modulating motor excitability in anesthetized rats. To examine the responses of tDCS-elicited plasticity, the motor evoked potential (MEP) and MEP input-output (IO) curve elicited by epidural motor cortical electrical stimulus were evaluated at baseline and after 30 min of anodal tDCS or cathodal tDCS. Furthermore, a paired-pulse cortical electrical stimulus was applied to assess changes in the inhibitory network by measuring long-interval intracortical inhibition (LICI) before and after tDCS. In the results, analogous to those observed in humans, the present study demonstrates long-term potentiation- (LTP-) and long-term depression- (LTD-) like plasticity can be induced by tDCS protocol in anesthetized rats. We found that the MEPs were significantly enhanced immediately after anodal tDCS at 0.1 mA and 0.8 mA and remained enhanced for 30 min. Similarly, MEPs were suppressed immediately after cathodal tDCS at 0.8 mA and lasted for 30 min. No effect was noted on the MEP magnitude under sham tDCS stimulation. Furthermore, the IO curve slope was elevated following anodal tDCS and presented a trend toward diminished slope after cathodal tDCS. No significant differences in the LICI ratio of pre- to post-tDCS were observed. These results indicated that developed tDCS schemes can produce consistent, rapid, and controllable electrophysiological changes in corticomotor excitability in rats. This newly developed tDCS animal model could be useful to further explore mechanical insights and may serve as a translational platform bridging human and animal studies, establishing new therapeutic strategies for neurological disorders.